Perjanjian Kerja Antara Pelaku Usaha Dengan Tenaga Kerja Dalam Perjanjian Hubungan Industrial - Bryllian Abraham Titihalawa; Barzah Latupono; Dezonda Rosiana Pattipawae (PATTIMURA Law Study Review, 2023)
ABSTRACT: An industrial relations dispute is a difference of opinion that results in a conflict between an entrepreneur or a combination of entrepreneurs and workers/laborers or a trade union/labor union due to disputes regarding rights, disputes over interests, and disputes over the termination of employment relations as well as disputes between trade unions/labor unions in only one company. The purpose of the agreement is none other than the purpose of the law itself, namely to provide protection and justice for the parties entering into the agreement. This research uses normative juridical research methods, namely library law research and because this research is carried out by having library materials. The approach in normative research is the Statute Approach and the Conceptual Approach. In this study, a descriptive-analytical type of research will be used. Work agreements are made in writing or verbally. Work agreements that are required in writing are carried out in accordance with applicable laws and regulations. Work agreements are divided into PKWT and PKWTT. PKWT is regulated to provide protection for workers, on the basis of the consideration that it does not occur where the appointment of workers is carried out through an agreement in the form of a PKWT for work that is continuous or is a permanent/permanent job of a business entity. PKWT can be done with a daily work agreement. Daily Work Agreements are carried out with the condition that the Worker/Labourer works less than 21 (twenty one) days in 1 (one) month. If the Worker/Labourer works 21 (twenty one) days or more for 3 (three) consecutive months or more, the Daily Work Agreement becomes invalid and the Employment Relations between Employer and Worker/Labourer by law change based on the PKWTT.